Vertical Transmission of Severe Acute Respiratory Syndrome Coronavirus 2: A Systematic Review - Yang, Ziyi; Liu, Yi (American Journal of Perinatology, 2020)
Objective The aim of this study is to summarize currently available evidence on vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).Study Design A systematic review was conducted following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analysis Statement.Results A total of 22 studies comprising 83 neonates born to mothers diagnosed with coronavirus disease 2019 were included in the present systematic review. Among these neonates, three were confirmed with SARS-CoV-2 infection at 16, 36, and 72 hours after birth, respectively, by nasopharyngeal swab real-time polymerase chain reaction (RT-PCR) tests; another six had elevated virus-specific antibody levels in serum samples collected after birth, but negative RT-PCR test results. However, without positive RT-PCR tests of amniotic fluid, placenta, or cord blood, there is a lack of virologic evidence for intrauterine vertical transmission.Conclusion There is currently no direct evidence to support intrauterine vertical transmission of SARS-CoV-2. Additional RT-PCR tests on amniotic fluid, placenta, and cord blood are needed to ascertain the possibility of intrauterine vertical transmission. For pregnant women infected during their first and second trimesters, further studies focusing on long-term outcomes are needed.Key Points
Keywords: severe acute respiratory syndrome coronavirus 2; coronavirus disease 2019; vertical transmission; neonate; systematic review